Вплив йодного дефіциту на тиреоїдний гормоногенез матері та плода - Бєлих, Н. А. (Clinical Endocrinology and Endocrine Surgery, 2012)
The article deals with the results of the neonatal screening of congenital hypothyroidism (n=46 579), regional epidemiological study which included interviewing of pregnant women, estimation of the median of urinary iodine, ultrasound evaluation of thyroid volumes (n=1052), study of the hypothalamic-thyroid status in pregnant women (n=252). It was demonstrated that insufficient iodine supplementation leads to the gestational hypothyroxinemia and neonatal hyperthyrotropinemia. The conclusion of the necessity of the iodine supplementation in preconception and antenatal period was made.